KONTRIBUSI PENERJEMAH PADA ZAMAN KEEMASAN ISLAM - M. Iqbal Dawami (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
History shows that a glory of a nation has something to do with its translation activities because those activities mean communicating cultural products of a nation to another. Islam has been doing it for centuries. Through these activities, Islam has its heyday. This paper aims at describing the historical phases of translation of non-Arabic works into Arabic in the Age of Classic between 17 and 19  century.